Treasure in clay: The Autobiography of Fulton J. Sheen - Sheen, Fulton J. (Doubleday and Company Garden City, New York, 1980)
The late Fulton Sheen relates his own rich and varied life story which comprised sixty years as one of America's best-loved Catholic priests, whose radio and television congregation numbered thirty million strong.
Keywords: Sheen, Fulton J. -- 1895-1979; Bishops -- United States; Bishops -- Catholic Church; Clergy -- Catholic Church